Performance of Heifers on Controlled Continuous Grazing Versus Continuous Grazing with Supplementation of Hay During the Lean Period - Mauria, S; Harsh, L N (Annals of Arid Zone, 2016)
The trial aimed at comparison' of performance of growing heifers in two systems viz., continuous controlled grazing and continuous controlled grazing with additional stall-feeding of green hay during the ean season. Hay conserved for stall-feeding was harvested from half portion of the grazing paddock. Stall-feeding of conserved hay resulted in better maintenance with increase in body weight during the lean season of normal rainfall years. No negative impact on vegetation was observed.